立筒仓悬挂式清洁机器人的建模与转动控制仿真 - 曹毅; 刁伟华; 于心俊 (Jixie chuandong)
A hanging robot developed to allow the clearing of hung up material in large silo is proposed.It is very important to design a controller with accuracy and rapidness to satisfy the revolving control for the robot.Firstly,without loss of generality,the physical model of the hanging robot and create its virtual prototype in ADAMS of MSC is simplified.Secondly,the co-simulation method is implemented by using ADAMS/Controls and MATLAB/Simulink for controlling the revolution of the robot.Finally,the plot of angular displacement and angular velocity of the simulation is obtained and analyzed.